Human Rights, Self-Formation and Resistance in Struggles against Disposability: Grounding Foucault's "Theorizing Practice" of Counter-Conduct in Bhopal. Issue 2 (2nd April 2016) - Odysseos, Louiza
Abstract : Theorising how human rights function as a liberal governing technology has undoubtedly been an important contribution of "governmentality studies". Such theorisation, however, has largely eschewed concerted examination of the mobilisation and impact of human rights in historically specific struggles. This has tended to divorce the theoretical concerns of critical rights scholarship from the specificity of political struggles, reifying rights and obscuring the agency of "the governed" in struggles against socio-economic disposability. Calling for greater attention to human rights' potential destabilisations of conduct, the article examines Foucault's work into forms of resistance to "power that conducts"—"counter-conduct"—which is increasingly inspiring wide-ranging analyses of resistances to conducting power. Bringing together the "theorising practice" of counter-conduct and the enduring campaigns for justice by survivors and activists of the 1984 Bhopal gas disaster, the article examines how human rights enable forms of self-formation that interrupt the subjectification of those constructed as disposable subjects. Illuminating survivors' intervention in their ethical self-transfiguration mitigates against the occlusion of the agency of the governed. Moreover, the article argues, the thinking of counter-conduct recalibrates Foucault's own methodological orientations away from an overwhelming focus on mechanisms of governmental power, towards the study of the counter-conductive practices of co-governing subjects.